1990
DOI: 10.1055/s-2006-961004
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Behavioural Effects ofMorinda citrifolia

Abstract: The traditional therapeutic indications for the use of Morinda citrifolia L. (Rubiaceae) have been investigated. The lyophilised aqueous extract of roots of M. citrifolia was evaluated for analgesic and behavioural effects in mice. The extract did not exhibit any toxic effects but did show a significant, dose-related, central analgesic activity in the writhing and hotplate tests; this effect was confirmed by the antagonistic action of naloxone. Furthermore, administration of M. citrifolia extract at high dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 3 publications
0
55
1
3
Order By: Relevance
“…Some researchers have shown that the aqueous extracts of the fruit and roots of the Noni plant have an antinociceptive effect via opioid receptors. 11,12) In the present study, these effects were not inhibited by pretreatment of NLX on the antinociceptive effect of the CHCl 3 -soluble phase. The CHCl 3 -soluble phase may therefore produce an antinociceptive effect without acting on opioid receptors.…”
Section: Discussioncontrasting
confidence: 41%
“…Some researchers have shown that the aqueous extracts of the fruit and roots of the Noni plant have an antinociceptive effect via opioid receptors. 11,12) In the present study, these effects were not inhibited by pretreatment of NLX on the antinociceptive effect of the CHCl 3 -soluble phase. The CHCl 3 -soluble phase may therefore produce an antinociceptive effect without acting on opioid receptors.…”
Section: Discussioncontrasting
confidence: 41%
“…A French research team has also studied the analgesic and sedative effects of M. citrifolia L. on mice through the writhing and hotplate tests. M. citrifolia L. root extract (1600 mg/kg) showed significant analgesic activity in the animals, similar to the effect of morphine (75% and 81% protection using M. citrifolia L. extract and morphine, respectively), and it also proved to be non-toxic (Younos et al, 1990).…”
Section: Analgesic Activitymentioning
confidence: 68%
“…Teniendo en consideración que, posterior a todo procedimiento quirúrgico bucal aparece un episodio doloroso, existe plena justificación para la utilización de medicamentos que controlan y reducen la duración y grado de dolor posoperatorio (Becker;Jung et al;Romera et al, 2000). La evidencia de que el fruto de Noni presenta efecto analgésico proviene de experimentos en animales, realizados por Younos et al (1990), Punjanon & Nandhasri (2005), Akihisa et al (2007), Deng et al (2007) y Dussossoy et al (2011). Según recientes investigaciones, la inhibición de las vías metabólicas de ciclooxigenasa y lipooxigenasa pueden ser las responsables de este efecto (Wang et al;Akihisa et al;Palu et al, 2004Palu et al, , 2012.…”
Section: Discussionunclassified